THE EFFECTIVENESS OF THE SOCIAL SECURITY PROVIDER (BPJS) PROGRAM IN HEALTH SERVICES AT SYARIFAH AMBAMI RATO EBU HOSPITAL, BANGKALAN REGENCY - Diana Hertati (DIA: Jurnal Administrasi Publik, 2021)
The community's need for BPJS health services is very important. Syarifah Ambami Rato Ebu (Syamrabu) Bangkalan Hospital as a health provider to improve the effectiveness of health services for the people of Bangkalan district. Based on the Undang-Undang Nomor 24 Tahun 2011 concerning the Social Security Provider (BPJS), the government organizes a national health insurance program through BPJS Kesehatan to ensure that all Indonesians are covered by health insurance. The purpose of this study was to describe and analyze the Effectiveness of the Social Security Provider (BPJS) Program in Health Services. This study uses qualitative methods with data collection techniques of observation, interviews, and documentation. Data analysis techniques are data collection, data condensation, data presentation, and drawing conclusions. This research is located in Syarifah Ambami Rato Ebu Hospital, Bangkalan. The results of this study are the resources, funds, facilities, and infrastructure used are effective, the number and quality of services produced are effective, the time limit for producing goods or services is effective, and the way to do it is already effective. The conclusion of this study is that health services for BPJS Inpatient Installation (IRNA) B Bawah at Syarifah Ambami Rato Ebu Hospital, Bangkalan Regency have been effective but not optimal.